(untitled) (Agroindustrial Science, 2025)
Phosphorus use efficiency is controlled by the manner in which the plant acquires and utilizes the nutrient under limiting conditions. This study evaluated biomass and P accumulation, partitioning, and remobilization processes, and their relationship with P utilization efficiency (PUTE) in maize. Three early and three late maturing maize genotypes were grown on a P-deficient soil, with limited (25 kg P2O5 ha-1) and optimal (50 kg kg P2O5 ha-1) P fertilization. The study identified genotypic variation among the tested maize genotypes for PUTE. Under P deficiency environments, late maturing genotypes showed the greatest amount of dry matter and P in vegetative organs and a less remobilization of biomass to grain. In contrast, early maturing genotypes maintained unchanged proportion of biomass and P partitioning into various organs and a higher P remobilization to grain, at both P levels. Regardless of P application rate, biomass and P remobilization to the grain was higher in early maturing genotypes (22 y 21 %) than in late ones (18 y 15 %). Greater variation on PUTE was linked to an enhanced dry matter partitioning in the plants and a higher proportion of P allocated into young and active tissue, under P-limited acid soils.